Zarządzanie finansami w Izbie Rzemieślniczej w Opolu - Dębicka-Fobke, Grażyna (The Management of Finances in the Chamber of Handicraft in Opole, 2006)
The finances of any company operating in free-market economy constitute the basis for its existence. Financial decisions are simply given the status of existential ones, which considerably testifies lo their significance. Social and economic changes, the reform of educational system caused increased interest of the handicraft trade self-government in the finance managing issues. Till now at subject matter of finance management by chambers of handicraft has not been an object of scientific research. There are 28 chambers of handicraft operating in Poland and associated in Polish Handicraftsmen's Union. This paper presents a general description of finance management in a medium-sized Polish chamber, namely the Handicraft Chamber in Opole. The main sources of financing handicraft chambers in Poland are the proceeds from educational id administrative services (rental of chamber-owned premises). The management of finances in the Chamber of Handicraft in Opole ought to be closely connected with promotional marketing campaign aiming at attracting possibly the highest number of students who want to learn trades recognized as handicraft and. eventually, take apprentice's examinations. In order to maximize the profits from educational services the following actions have been taken: i The officials from the Department o Education, Self-government Affairs and Health and Safety Inspectorate arrange meetings with junior high school children encouraging them to learn the handicraft trades. The Chamber of Handicraft takes active part in educational fairs presenting the advantages of handicraft trades New materials promoting the study of handicraft have been compiled and are sent to schools, guilds and master instructors. The Chamber sends information brochures and leaflets to apprentices who already meet the retirements permitting them to take master examinations encouraging them to do these emulations. The fees for apprentice and master examinations have been increased. Skillful management of finances in the chambers has a great influence on their further activity. These units of economic self-government play a considerable part in the handicraft community. One of the main tasks of these units in accordance with the article 7 of handicraft law section 5 is participation in performing the tasks of the educational system in order to ensure qualified staff for handicraft. Will all these actions taken by the Chamber of Commerce secure making a profit in 2005? Although the odds are that they will, it still remains to be seen. In order to be able to answer the above question, the proceedings of the Chamber should be still observed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 150-159